Skala c.o.r.e.: Pengukur Kreativitas yang Benar-Benar Kreatif (Komentar terhadap Skala C.0.R.E. sebagai Alternatif Mengukur Kreativitas: Suatu Pendekatan Kepribadian) - Tjundjing, Sia (ANIMA Indonesian Psychological Journal, 2002)
Although research on creativity has been spearheaded by Guilford since 1979, a concensus of a standardized definition is not yet reached. Generally speaking, there are two approaches toward creativity, namely aptitude approach and personality characteristics approach (Albert & Runco, 1987). Suharnan (2002) prefered the personality characteristics approach and make a c.o.r.e. scale to measure creative spirit. Some weaknesses and shortages in structuring, exposing, and discussion of research results cast doubt on the credibility of the c.o.r.e. scale. The theoretical, methodological, and statistical analysis weaknesses are discussed.